Ответ:
[tex](a-b)(a+b)((a-b) ^ { 2 } +(a+b) ^ { 2 } )= (a ^ { 2 } -b ^ { 2 } )(a ^ { 2 } -2ab+b ^ { 2 } +a ^ { 2 } +2ab+b ^ { 2 } ) = ( { a }^{ 2 } - { b }^{ 2 } ) (2a ^ { 2 } +2b ^ { 2 } )= 2a ^ { 4 } -2b ^ { 4 } = 2(a ^ { 4 } -b ^ { 4 } )[/tex]
Объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex](a-b)(a+b)((a-b) ^ { 2 } +(a+b) ^ { 2 } )= (a ^ { 2 } -b ^ { 2 } )(a ^ { 2 } -2ab+b ^ { 2 } +a ^ { 2 } +2ab+b ^ { 2 } ) = ( { a }^{ 2 } - { b }^{ 2 } ) (2a ^ { 2 } +2b ^ { 2 } )= 2a ^ { 4 } -2b ^ { 4 } = 2(a ^ { 4 } -b ^ { 4 } )[/tex]
Объяснение: